Private Health Insurance and Plans Company Quality Performance Index: comparative analysis of the change in the evaluation methodology (Research, Society and Development, 2022)
Aim: To analyze comparatively the results of the Private Health Insurance and Plans Company Quality Performance Index (IDSS) in the evaluations of the base year 2016 and 2017, given the methodology changes in the Private Health Insurance and Plans Performance Evaluation Program (PQO). Methods: This is an observational, analytical, retrospective study that compared the performance results of private health companies in the old methodology, base year 2016, and in the new methodology, base year 2017, segregated by modality and size of the operator. The data were analyzed using the Wilcoxon test with R software. Results: It was found that the change in methodology significantly reduced the overall IDSS score with greater emphasis on three of the four dimensions, namely: Quality in Health Care, Guarantee of Access, and Management and Regulation. This reduction occurred among all sizes of private health companies, with the greatest amplitude among small companies, and significant reduction among all private health insurer type, except for private health insurer. Conclusion: The findings of this study indicate that the changes in the methodology impacted the performance score of the operators, especially the small ones. It suggests the need to understand the impacts on the supplementary health sector and the benefits of the methodology change for the health system.